The Advantages of Tactical Games and Cooperative Learning Models in Football Shooting Technique Skills - Rahmalia, Apriyanti; Ala, Faridatul' (Universitas Majalengka, 2023)
Physical education is an educational process that utilizes physical activity to produce holistic changes in individual quality, both physically, mentally and emotionally. One of the materials provided in physical education, sports and health subjects for MTS school students is the Big Ball Game, namely the Football Game. To improve football shooting technique skills, researchers will apply two models in their learning: cooperative learning and tactical games. The research method used in this research is the experimental method. The design used is a pre-test and post-test group design. The data analysis method used the t-test; the research subjects were 20 students at MTs N 6 Model Padang who participated in football extracurriculars. The results of data analysis show that: 1). The effectiveness of the cooperative learning model significantly improved the football shooting technique skills of MTS N 6 Model School students in Padang City (count = 7.12 > ttable = 2.27). 2). The effectiveness of the tactical games learning model significantly improved the football shooting technique skills of MTS N 6 Model Padang City School students (t-count = 9.45 > t-table = 2.27). 3) The effectiveness of the cooperative learning model is no better than the tactical games learning model group in improving the football shooting technique skills of MTS N 6 Model Padang City School students (tcount = 1.48 < ttable = 1.73).